Copy, “Anomalous” Markings, and Emergence of the Refrain in Galician--Portuguese Lyric Manuscripts (Cancioneiro da Ajuda, Lisboa) - Arbor Aldea, Mariña (Madrygal. Revista de Estudios Gallegos, 2020)
The edition of the cantigas of the Cancioneiro da Ajuda (A) and the study of its subject matter and organization presents a problem when dealing with the poems with refrains: how this structural element is marked and identified during the process of copy. This paper analyses different passages that present anomalous markings (in some cases corrected in the margins, where technical notes have also been added), poems with refrains of dubious authorship and meaning, and their distribution in the manuscript. Our purpose is to verify how refrains work and which years mark their emergence, and if (and why) they appear in sections of the manuscript identified by previous scholarship as ‘conflict zones’ of the unstable copy process of a cancioneiro, areas copied after a certain moment using heterogeneous sources that did not pass the same review process as the materials of its first sections.
Keywords: Refrains; Cancioneiro da Ajuda; Manuscript Tradition; Galician-Portuguese Profane Lyric